Continuous heavy metal removal from palm oil mill effluent using natural ceiba pentandra packed-bed column - Afzaal, M. (Trans Tech Publications Ltd, 2014)
Packed bed column studies were carried out to evaluate the performance of natural Ceiba pentandra (L). Gaertn. (kapok) for the heavy metal removal from Palm Oil Mill Effluent (POME) under varying flow rate (5-10 ml/min) and packing density (0.04-0.08 g/cm3). A multilevel factorial design based on Packing density and flow rate of the influent was developed. Maximum metal reductions for Fe, Mn and Zn were 2.06 ppm, 0.081 ppm, and 0.064 ppm respectively obtained at 0.08 g/cm3 packing density and 5 ml/min flow rate. The results suggest the suitability of raw kapok fiber for low-cost removal of heavy metals. Â© 2014 Trans Tech Publications, Switzerland.